2018
DOI: 10.1029/2018gl078114
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the Mesoarchean Emergence of Continental Crust in the Coorg Block, Southern India

Abstract: The emergence of Earth's continental crust above sea level is debated. To assess whether emergence can be observed at a regional scale, we present zircon U‐Pb‐Hf‐O isotope data from magmatic rocks of the Coorg Block, southern India. A 3.5‐Ga granodiorite records the earliest felsic crust in the region. Younger phases of magmatism at 3.37–3.27 and 3.19–3.14 Ga, comprising both reworked crust and juvenile material, record successive crustal maturation. We interpret an elevation in δ18O through time as an increas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…As aconclusion, we summarize that the observed levels of solar wind fluctuations around the ion characteristic scale generally follow theoretical linear relations for KAWs. Our results are consistent with the previous studies (Chen et al 2013a;Lacombe et al 2017;Grošelj et al 2018;Roberts et al 2018). Moreover, we demonstrate that aspread of the observed/predicted values of KAW normalized fluctuations is not caused by either random or systematic errors of measurements.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…As aconclusion, we summarize that the observed levels of solar wind fluctuations around the ion characteristic scale generally follow theoretical linear relations for KAWs. Our results are consistent with the previous studies (Chen et al 2013a;Lacombe et al 2017;Grošelj et al 2018;Roberts et al 2018). Moreover, we demonstrate that aspread of the observed/predicted values of KAW normalized fluctuations is not caused by either random or systematic errors of measurements.…”
Section: Discussionsupporting
confidence: 93%
“…They derived relations between density and parallel magnetic field fluctuations and for the Alfvén ratio, R A (R A is the ratio between the kinetic and magnetic energy of fluctuations). Roberts et al (2018) applied the theoretical formulae of Zhao et al (2014) for R A and the Boldyrev et al (2013) prediction forR nB and found that kinetic range fluctuations measured by the Magnetospheric Multiscale (MMS) mission in Earth's magnetosheath are consistent with kinetic Alfvén-like turbulence. Recently, Grošelj et al (2018) analyzed high-cadence magnetic field (MMS and Cluster) and plasma measurements (MMS) in the solar wind and reported the agreement between KAW linear predictions of three dimensionless ratios, compressibility,R nB , and ( ) ( )…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Main lithological associations reported here are TTGs and transitional TTGs, bimodal volcanic-sedimentary greenstone sequences, and composite plutons of sanukitiods and anatectic granites (Ramakrishnan and Vaidyanadhan, 2008;Jayananda et al, 2013, 2018 andreferences therein). Even though the Dharwar craton for long was divided into two or even three blocks-the eastern and the western Dharwar, recent studies (see Peucat et al, 2013;Ishwar Kumar et al, 2013;Santosh et al, 2015;Roberts and Santosh, 2018;Jayananda et al, 2018 and references therein) favour it to be an amalgamation of several micro-blocks (western, central, eastern, Coorg and Karwar) with independent thermal record and evolutionary histories. Peng et al (2019) envisaged the Dharwar craton to be a trinity of Archean crustal architecture ('sandwich' structure), comprising (i) 2700-2500 Ma-dominated upper crust, (ii) 3400-2900 Ma-dominated middle crust, and (iii)~2560-2500 Ma anatectic lower crust.…”
Section: Geological Backgroundmentioning
confidence: 99%